ANALISIS PENGARUH ANGGARAN PENDIDIKAN, ANGGARAN KESEHATAN, DAN KEMISKINAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI INDONESIA - Djohan, Septiani; Saptono, Ari; Iranto, Dicky (Yayasan Education and Social Center, 2023)
The aim of this study is to find out how the Education Budget, Health Budget and Poverty level influence the Human Development Index (HDI) in Indonesia. The analytical method applied is the use of panel data regression analysis with a fixed effect model approach using Eviews 9 software. From the analysis carried out, it can be concluded that partially, the Education Budget has a positive influence on HDI in Indonesia, while the Health Budget has a positive influence that is not has sufficient statistical significance. Simultaneously, the Education Budget, Health Budget and Poverty have a significant effect on HDI in Indonesia. Overall, the Education Budget, Health Budget and Poverty together contribute 84.7697% to the HDI in Indonesia, while the remainder is influenced by other variables not included in the regression model